The Effects of Enhancing Health Literacy Program on Falls Prevention Behaviors among Village Health Volunteer in a Community, Nakhon Ratchasima Province - Pensuk, Pannarat; Valaisathien, Jantakant; Thangtham, Natthanaree (Journal of the office of disease prevention and control 9 Nakhon Ratchasima, 2025)
This study was a quasi-experimental, one-group pretest-posttest design. The objective of this research was to study the effect of a health literacy program on fall prevention among the elderly, focusing on village health volunteers (VHVs) in a community in Nakhon Ratchasima Province. The sample group included VHVs from the area served by Nongkham Health Promoting Hospital in Nong Rawiang Subdistrict, Phimai District, Nakhon Ratchasima Province. Fifty participants were selected based on inclusion criteria, and the program was implemented over an 11-week period. Data collection was performed before and after the program using questionnaires. The data were analyzed using percentages, mean, standard deviation, and paired sample t-test to compare the pretest and posttest mean scores. The results showed that after joining the program, the VHVs had significantly higher knowledge about fall prevention in the elderly (p < 0.05). Their behavior in helping to prevent falls also improved significantly (p < 0.05). Therefore, this health literacy program for fall prevention in the elderly that was used with VHVs should be applied to caregivers of elderly patients with other conditions. Healthcare workers can also utilize this program for developing, promoting, and preventing physical deterioration in the elderly, addressing fall prevention issues, and other aspects of physical decline.